Barriers to antiretroviral treatment initiation : the case of a rural area in the KwaZulu-Natal region, South Africa - (:unkn) unknown (My University, 2014)
Antiretroviral treatments (ART) have been available in sub-Saharan Africa for more than ten years.Their use was initially targeted with the strict aim to control severe morbidity in individuals with an advancedHIV disease. International guidelines for initiating ART have subsequently evolved as clinical andepidemiological studies highlighted the therapeutic and preventive benefits of early ART initiation. Randomizedtrials are currently underway in several southern African countries to measure the benefits of the universal“Test and Treat” approach on HIV incidence in a community. However, ART coverage is still far from optimal insub-Saharan Africa, especially in South Africa where 6.3 millions of individuals are living with HIV. We thusaimed to better understand what are the barriers to ART initiation by focusing on a rural area heavily affectedby HIV in the province of KwaZulu-Natal, South Africa. We first briefly described the journey HIV-infectedindividuals embark on, from entry into a large HIV treatment and care programme to ART initiation. Then wemeasured the temporal evolutions of ART initiation rates according to the changes of clinical guidelines. Wefinally identified some barriers to ART initiation linking data from the HIV care programme with those from ademographic surveillance system. The results of this thesis will help to better understand the issues relative toaccess to ART that might arise with the universal “Test and Treat” approach, especially in South Africa.
Keywords: African Research